The Isoflavone Contents of Devon 1 Soybeans during Fermentation and Processing into Soybean-Tempeh Steamed Buns - Amanda Villelie Sudarmin; Christina Mumpuni Erawati; Tjandra Pantjajani; Stephanie Belinda Wijaya; Pandu Salim Hanafi; Mariana Wahjudi (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2025)
Abstract—The soybean Devon 1 variety is a superior variety developed in Indonesia. The isoflavone content makes this soybean a top choice for a functional food. However, fermenting soybeans into tempeh and processing them into other products can affect the final isoflavone content. The objective of this study was to analyze the total isoflavone and its derivatives content in Devon 1 soybeans, soybean tempeh, soybean tempeh flour, and buns made from tempeh flour. The content of each isoflavone type was determined by high-performance liquid chromatography at λ249 and λ260 nm wavelengths. The buns were made from tempeh flour with variations of tempeh flour substitution of 0, 10, 20, and 30%. The results showed that the fermentation of Devon 1 soybeans and further processing of tempeh significantly altered the isoflavone components and content. The concentrations of daidzin and genistin in tempeh were decreased, while daidzein and genistein were increased. Further processing of tempeh into flour increased all isoflavone levels significantly, which might be caused by the isoflavone transformation during drying and enzymatic activity. Substitution of wheat flour with soybean tempeh flour increased these four isoflavones content of the buns. Therefore, tempeh flour made from Devon 1 soybeans has the potential to be used as a functional food ingredient rich in bioactive compounds that promote health. Keywords: flour, heat, isoflavone aglycones, isoflavone glycoside, soybean tempeh Abstrak—Kedelai varietas Devon 1 merupakan varietas unggul yang dikembangkan di Indonesia. Kandungan isoflavonnya menjadikan kedelai ini sebagai pilihan utama untuk pembuatan pangan fungsional. Namun, proses fermentasi kedelai menjadi tempe, serta pengolahan lebih lanjut menjadi berbagai produk turunan dapat memengaruhi kandungan akhir isoflavonnya. Penelitian ini bertujuan untuk menganalisa kandungan total isoflavon dan turunannya pada kedelai Devon 1, tempe kedelai, tepung tempe kedelai, serta bakpao yang dibuat dari tepung tempe. Kandungan masing-masing jenis isoflavon diuji menggunakan kromatografi cair kinerja tinggi pada panjang gelombang λ249 dan λ260 nm. Adapun bakpao dibuat dari tepung tempe dengan variasi substitusi tepung tempe sebesar 0, 10, 20, dan 30%. Hasil penelitian ini menunjukkan bahwa fermentasi kedelai Devon 1 dan pengolahan tempe lebih lanjut secara signifikan mengubah komponen dan kandungan isoflavon. Kandungan daidzin dan genistin dalam tempe menurun, sedangkan kandungan daidzein dan genisteinnya mengalami peningkatan. Pengolahan tempe menjadi tepung lebih lanjut meningkatkan seluruh kandungan isoflavon secara signifikan, yang kemungkinan disebabkan oleh transformasi isoflavon selama proses pengeringan dan aktivitas enzimatis. Substitusi tepung terigu dengan tepung tempe meningkatkan kandungan keempat jenis isoflavon pada bakpao. Dengan demikian, tepung tempe kedelai Devon 1 berpotensi digunakan sebagai bahan pangan fungsional yang kaya akan senyawa bioaktif untuk menunjang kesehatan. Kata kunci: aglikon isoflavon, glikosida isoflavon, pemanasan, tempe kedelai, tepung